Innovation in public administration: Itineraries of Brazilian scientific production and new research possibilities - Grazielle Sucupira; Flávio Saab; Gisela Demo; Paulo Henrique Bermejo (Innovation & Management Review, 2019)
Purpose: The subject of innovation in public service has been gaining attention in Brazilian scientific practice and production. This paper aims to identify national studies on innovation in public administration and increase the level of knowledge about the subject, as well as to inspire new research and promote advances in theoretical and practical knowledge about innovation in the public sector. Design/methodology/approach: The present study has a descriptive purpose, quantitative nature and was performed through a bibliometric study based on the protocol proposed by Cronin et al. (2008). Documentary data were collected from scientific articles, and quantitative techniques for descriptive statistics were used to analyze the results. Were selected Brazilian scientific journals classified with Qualis equal to or higher than B1, in the area of Public Administration and Business, Accounting and Tourism, in the quadrennium 2013-2016; a total of 164 journals searched. Findings: The results herein indicate a research gap that should be filled by more theoretical studies. Also, they point to the need for multimethod research studies that promote the evaluation of product and process innovation, especially related to the phases of invention and implementation. Originality/value: Few studies have covered public administration and, especially, innovation reviews; none of these studies focused on innovation in the Brazilian public sector, as proposed by this research; the period of analysis and coverage of journals used as search criteria also differ from other reviews in the area of innovation and public sector.
Keywords: 650; Innovation; Innovation in the public sector; Public sector